Conventional right handed laryngoscope blade used as left handed blade: an experience with a case of mass in right side of oral cavity - Parajuli, Bashu Dev; Limbu, Trishant (Journal of Society of Anesthesiologists of Nepal, 2016)
Approach to management of anticipated difficult airway depends upon difficulty anticipated and availability of resources (expertise and instruments). Awake fibreoptic intubation is the preferred method to secure an anticipated difficult airway. However, availability of the instrument, expertise to use and patient cooperation should be considered. A conventional right handed laryngoscope blade can’t be negotiated when the airway pathology involves part or whole of the right side, compressing the airway structures towards the left. In such cases, a left-handed laryngoscope blade helps to displace the tongue and the right-sided lesion to provide an unobstructed left sided view of the larynx. Here we describe a case of difficult airway with mass in right side of the neck region with tracheal deviation to left, for which right handed conventional laryngoscope blade could not be inserted due to extension of mass up to the right side of the tongue. On the second attempt, the usual right hand laryngoscope blade was held on right hand and inserted from the left side displacing the tongue to right side and bougie held in left hand was used to guide tracheal intubation.